Effectiveness of family support health education intervention to improve health-related quality of life among pulmonary tuberculosis patients in Melaka, Malaysia - Saidi, Syafiq Sidqi; Abdul Manaf, Rosliza (BMC, 2023)
Background: Pulmonary Tuberculosis (PTB) is an important public health problem in Malaysia. In this country, limited research has been carried out on the impact of the disease on the health-related quality of life (HRQoL). Family support interventions had been shown to be effective in improving the PTB treatment outcomes. Objectives: This study aims to determine the effectiveness of a newly developed Family Support Health Education (FASTEN) intervention in improving the health-related quality of life (HRQoL) among PTB patients in Melaka, as compared to the current conventional disease management. Materials and methods: A single-blinded, randomized controlled field trial study design was conducted in Melaka from September 2019 until August 2021, involving newly diagnosed PTB patients. The participants were randomized either into the intervention group (FASTEN intervention) or into the control group (conventional management). They were interviewed by using a validated questionnaire that includes the Short Form 36 Health Survey version 2 (SF-36v2), at three time points: at diagnosis, two months and six months after diagnosis. Data were analyzed using IBM SPSS Statistics for Windows version 24. The Generalized Estimating Equations (GEE) analysis was used to evaluate the effectiveness of the intervention, in terms of the HRQoL score difference between the groups, adjusted for baseline covariates. Results: The HRQoL among PTB patients was lower than the HRQoL of general Malaysian population. Among the total 88 respondents, the three lowest HRQoL domains scores at baseline were Social Functioning (SF), Role limitation due to Physical condition (RP) and Vitality (VT) with the median (IQR) scores of 27.26 (10.03), 30.21 (11.23) and 34.77 (8.92) respectively. The median (IQR) for Physical Component Score (PCS) was 43.58 (7.44) and for Mental Component Score (MCS) was 40.71 (8.77). There were significant difference in the HRQoL median scores between the intervention group compared to the control group, as the Physical Functioning (PF) (p=0.018), RP (p<0.001).